Wastewater Treatment: Current and Future Techniques - Mojiri, Amin; Bashir, Mohammed J.K (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book examines the state-of-the-art water and wastewater treatment methods that can be applied to develop a sustainable treatment technique in the future. Of the several high-quality articles submitted, twelve were published after the peer-review process, with an acceptance rate of 59 percent. In the first section of this book, the articles include the occurrence and removal of emerging contaminants in water bodies. Moreover, the presence of perfluoroalkyl and polyfluoroalkyl substances (PFASs) in water sources is discussed in detail. Subsequently, the removal of polycyclic aromatic hydrocarbons (PAHs), pharmaceuticals and personal care products (PPCPs), and dye with different physicochemical methods is investigated. In another section of this book, the removal of ammonia with anaerobic ammonium oxidation (anammox) is studied. Additionally, the elimination of heavy metals using the adsorption process, as an effective method, is discussed. Moreover, the performance of membrane bioreactors in the elimination of pollutants from landfill leachate is investigated in another article in this book. In addition to this, green and sustainable wastewater technologies (GSWTs) have recently attracted the attention of researchers. Therefore, nanoremediation and microalgae-based systems are discussed as the GSWTs.